STRATEGI PENGEMBANGAN ULOS MELALUI UKM DI KECAMATAN TARUTUNG KABUPATEN TAPANULI UTARA - Novia Hepriani Pane; Zaili Rusli (Journal Publicuho, 2021)
The circulation of screen printing Ulos and the Covid 19 pandemic caused a negative impact on Ulos SMEs in Tarutung District which could threaten the sustainability of small industrial businesses. The strategic importance is right in accordance with Ulos and its ancestral values by the Small and Medium Enterprises Cooperative Trade Office and the North Tapanuli Dekranasda. The purpose of this research is to see how the Ulos development strategy through SMEs is carried out by the Small and Medium Enterprises Cooperative Trade Office of North Tapanuli Regency and what factors influence the Ulos development strategy. The research method used is a qualitative approach with descriptive data, followed by a strategy formulation using the SWOT analysis method. Based on research and discussion, it was found that the Ulos Development Strategy through SMEs in Tarutung District, North Tapanuli Regency had not been implemented optimally, this was influenced by limited capital and the less than optimal role of the government.